Greater genetic diversity is needed in human pluripotent stem cell models - Sulagna Ghosh; Ralda Nehme; Lindy E. Barrett (Nature Communications, 2022)
While there are a growing number of human pluripotent stem cell repositories, genetic diversity remains limited in most collections and studies. Here, we discuss the importance of incorporating diverse ancestries in these models to improve equity and accelerate biological discovery.